2010
DOI: 10.1021/ja1071515
|View full text |Cite
|
Sign up to set email alerts
|

A Water-Soluble Xe@cryptophane-111 Complex Exhibits Very High Thermodynamic Stability and a Peculiar 129Xe NMR Chemical Shift

Abstract: The known xenon-binding (±)-cryptophane-111 (1) has been functionalized with six [(η(5)-C(5)Me(5))Ru(II)](+) ([Cp*Ru](+)) moieties to give, in 89% yield, the first water-soluble cryptophane-111 derivative, namely [(Cp*Ru)(6)1]Cl(6) ([2]Cl(6)). [2]Cl(6) exhibits a very high affinity for xenon in water, with a binding constant of 2.9(2) × 10(4) M(-1) as measured by hyperpolarized (129)Xe NMR spectroscopy. The (129)Xe NMR chemical shift of the aqueous Xe@[2](6+) species (308 ppm) resonates over 275 ppm downfield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
100
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 31 publications
1
100
0
Order By: Relevance
“…The development of high-affinity Xe-binding cages is an area of active investigation and is critical to the burgeoning field of xenon biosensing (16,37,38). Synthetic host molecules designed to bind xenon in cells or in vivo must compete against a wide variety of biological substrates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of high-affinity Xe-binding cages is an area of active investigation and is critical to the burgeoning field of xenon biosensing (16,37,38). Synthetic host molecules designed to bind xenon in cells or in vivo must compete against a wide variety of biological substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Recent X-ray crystallographic studies have shown that the internal volume of trisubstituted cryptophane-A derivatives can vary by more than 20%, depending on the size of the encapsulated guest (12). Several cryptophane-A derivatives have been synthesized and shown by isothermal titration calorimetry (ITC), fluorescence quenching, and NMR studies to exhibit xenon association constants as high as 33;000 AE 3;000 M −1 at 293 K in phosphate-buffered water (13)(14)(15)(16). Herein, we report a previously unsynthesized cryptophane-A derivative, tris-(triazole ethylamine) cryptophane (TTEC), with superior xenon-binding characteristics.…”
mentioning
confidence: 99%
“…12 Another strategy was the metalation of the six arene rings of cryptophane-111 by [Cp*Ru] + moieties leading to cryptophane salts which exhibit a very high water solubility at physiological pH and the highest xenon affinity ever reported. 10 More recently, a new cryptophane skeleton has been developed : cryptophane with two ethylenedioxy linkers and the third linker of the propylenedioxy type bearing a unique secondary alcohol. 13 A second solubilizing or functional group can therefore be selectively introduced, facilitating the synthesis of new molecular platforms with reduced risks of creation of diastereomers.…”
mentioning
confidence: 99%
“…An important concern can also be the ability of the biosensor to cross the cell membrane. Considering all these requirements, various host structures have been synthesized during the recent years: cryptophanes, 10 cucurbiturils, 14 cucurbituril-based rotaxanes, 15 pillararenes, 16 Fe 4 L 6 cages 14 (respectively 1 to 5 in Fig. 3 been conceived following two strategies.…”
mentioning
confidence: 99%
“…Indeed, the boronic acid function is an electron-withdrawing group, whereas the phenol group is an electron-donating group. The cryptophane-111 structure was chosen, as 1) it displays the highest affinity for xenon both in organic solvents [10] and water, [11] 2) tiny chemical modifications on the aromatic rings are expected to strongly influence the chemical shift of caged xenon, and 3) since it is the smallest cryptophane representative, although far from simple, theoretical calculations should be more straightforward. Moreover, several boronic functionalities can be grafted on a cryptophane-111 core to form, after oxidation, different molecular cages.…”
mentioning
confidence: 99%